Psychological, pharmacological, and combined smoking cessation interventions for smokers with current depression: A systematic review and meta-analysis. - Roberto Secades-Villa; Alba González-Roz; Ángel García-Pérez; Elisardo Becoña (PLoS ONE)
We conducted a systematic literature review and meta-analysis (ID: CRD42016051017) of smoking cessation interventions for patients with current depression. We examined the effectiveness of smoking cessation treatments in improving abstinence rates and depressive symptoms. The following electronic databases were used for potentially eligible studies: PUBMED, PSYCINFO, DIALNET and WEB OF KNOWLEDGE. The search terms used were: smoking cessation, depressive disorder, depression, mood, depressive, depressed, smoking, smokers, nicotine, nicotine dependence, and tobacco cigarette smoking. The methodological quality of included studies was assessed using the Effective Public Health Practice Project Quality assessment tool (EPHPP). Of the 6,584 studies identified, 20 were eligible and included in the review. Trial designs of studies were 16 randomized controlled trials and 4 secondary studies. Studies included three types of intervention: psychological (6/30%), pharmacological (6/30%) or combined (8/40%). Four trials comprised special populations of smokers. Four studies received a strong methodological quality, 7 were scored as moderate and 9 studies received a weak methodological rating. Analyses of effectiveness showed that smoking cessation interventions appear to increase short-term and long-term smoking abstinence in individuals with current depression. Subgroup analyses revealed stronger effects among studies that provided pharmacological treatments than in studies using psychological treatments. However, the evidence is weak due to the small number of studies. Smoking abstinence appears to be associated with an improvement in depressive symptoms. Heterogeneity in protocols in similar types of treatment also prevent firm conclusions being drawn on the effectiveness of any particular treatment model to optimally manage abstinence among depressed smokers. Further research is required to strengthen the evidence base.